2013
DOI: 10.3747/co.20.1197
|View full text |Cite
|
Sign up to set email alerts
|

Responses by Breast and Prostate Cancer Patients to Out-Of-Pocket Costs in Newfoundland and Labrador

Abstract: Purpose: Cancer patients face substantial care-related out-of-pocket (oop) costs that may influence treatment decisions, attitudes, and use of drug- or appointment-related cost-saving strategies. We examined the relationship between oop costs and care-related responses by patients. Methods: We surveyed 170 prostate and 131 breast cancer patients presenting at clinics or support groups, or listed on the cancer registry in Newfoundland and Labrador. Results: In the 3-month period before the survey, 18.8% of pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Out-of-pocket payments and changes to employment were common among participants in this study. While research in cancer care has also identified out-of-pocket payments as an unanticipated consequence of illness for Canadian patients (Housser et al 2013;Longo and Bereza 2011), unlike cancer treatments which are often time-limited, the participants in our study anticipated these costs for the duration of their children's lives. There was also a gendered aspect of this finding, as the majority of participants were women (N = 15) and many reported either decreasing their employment to part-time or leaving the workforce entirely in order to care for their children during times when they were hospitalized or to attend numerous appointments.…”
Section: Discussionmentioning
confidence: 99%
“…Out-of-pocket payments and changes to employment were common among participants in this study. While research in cancer care has also identified out-of-pocket payments as an unanticipated consequence of illness for Canadian patients (Housser et al 2013;Longo and Bereza 2011), unlike cancer treatments which are often time-limited, the participants in our study anticipated these costs for the duration of their children's lives. There was also a gendered aspect of this finding, as the majority of participants were women (N = 15) and many reported either decreasing their employment to part-time or leaving the workforce entirely in order to care for their children during times when they were hospitalized or to attend numerous appointments.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of financial adjustments needed varies in all settings but more extreme measures such a refinancing homes [ 37 ] or house repossessions [ 23 ] have been reported in both the US and the UK. Forgoing treatment or rationing medications because of cost has been described in other settings [ 6 , 38 – 42 ] although Housser et al [ 43 ] recently reported that care-related cost savings were generally rare among breast and prostate patients in Canada. In our setting, patients were sometimes referred to OSWs to avoid this but none of the patients interviewed reported making treatment decisions based on cost/affordability.…”
Section: Discussionmentioning
confidence: 99%
“…Third, our findings illustrated the potential financial burden of using healthcare services. Previous research on out‐of‐pocket costs for Canadians has mainly focused on cancer patients (e.g., de Oliveira et al, ; Housser et al, ). Unlike cancer patients, who will experience these costs for the duration of their disease treatment, individuals with ID will be obligated to these costs for their adult years and the costs will likely rise with increasing age and frailty.…”
Section: Discussionmentioning
confidence: 99%